1969
DOI: 10.1177/004051756903900201
|View full text |Cite
|
Sign up to set email alerts
|

Needle Heating during High-Speed Sewing

Abstract: A review of the literature and extensive field interviews have been conducted on the subject of needle heating in high-speed sewing. As a result of this investigation, a survey of the current state of the art and knowledge available in the field has been completed and is presented in the following categories: (1) the nature of the problem and the difficulties which arise in commercial operations; (2) quantitative methods of measuring needle temperatures; (3) the influence of machine factors such as sewing spee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 5 publications
1
12
0
Order By: Relevance
“…All studies showed that fabric mechanical behaviour depends on finishing parameters (kind of finishing, temperature, time) and seaming parameters. The most studied seaming parameters are the needle heating, the needle point shape and the needle surface treatment [3,5,7,10]. We have studied the effect of finishing on fabric mechanical properties and its influence on seam quality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All studies showed that fabric mechanical behaviour depends on finishing parameters (kind of finishing, temperature, time) and seaming parameters. The most studied seaming parameters are the needle heating, the needle point shape and the needle surface treatment [3,5,7,10]. We have studied the effect of finishing on fabric mechanical properties and its influence on seam quality.…”
Section: Discussionmentioning
confidence: 99%
“…Needle temperature increased more for dyed and finished fabrics than for fabrics that are only bleached. In addition, the types of finishing treatment generated different heating behaviours [7].…”
Section: Effects Of Finishing Treatments On Fabric Mechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This high temperature weakens the thread, since thread tensile strength is a function of temperature [1]. and infrared pyrometer [1,2] These experimental methods are accurate and reliable [2,3].…”
mentioning
confidence: 99%
“…Experiments are in progress along this line, the details of which will be published in the near future. [ 1,2,[6][7][8]12] have an important effect on needle temperature and forces opposing needle penetration. However, the relationship between fabric parameters and needle temperature or forces opposing needle penetration has not been determined, and some information on this subject is given here.…”
mentioning
confidence: 99%